2008
DOI: 10.1111/j.1526-4637.2008.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Spinal Diagnostic and Treatment Procedures

Abstract: A B S T R A C TBackground. Spinal intervention procedures are widely practiced. Complications are sometimes described in case reports, but the full spectrum of possible complications has not been comprehensively publicized. The fact that certain complications continue to occur suggests that practitioners may not be fully aware of the nature of possible complications and how to recognize warning signs.Objectives. To highlight the nature of potential complications of spine interventions and to assist practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
218
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(226 citation statements)
references
References 77 publications
(83 reference statements)
0
218
1
7
Order By: Relevance
“…A recent systematic review has found that there was no significant difference between transforaminal and caudal epidural injection [39]. Transforaminal injection of steroids can be hazardous [40][41][42], and especially if carelessly performed. Guidelines for the safe conduct of transforaminal injections have been published by the International Spinal Intervention Society [43], emphasizing particularly the need to be vigilant for unintended, intra-arterial injection of particulate steroids.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review has found that there was no significant difference between transforaminal and caudal epidural injection [39]. Transforaminal injection of steroids can be hazardous [40][41][42], and especially if carelessly performed. Guidelines for the safe conduct of transforaminal injections have been published by the International Spinal Intervention Society [43], emphasizing particularly the need to be vigilant for unintended, intra-arterial injection of particulate steroids.…”
Section: Discussionmentioning
confidence: 99%
“…The zygapophysial joint was identified as a pain source with one or two medial branch blocks at different appointments in the practice, each with about 1 ml of bupivacaine (0.25%) and 20 mg triamcinolone. Injections were performed with fluoroscopic visualization using established techniques [1]. A positive response to the medial branch block required at least 50% pain relief.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the most accepted method [1] for diagnosing zygapophysial joint pain is controlled medial branch blocks. They are used to test if the pain stems from the zygapophysial joint because the medial branch innervates it [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations